AN ANALYSIS ON ESP STUDENTS’ ONLINE LEARNING NEEDS: BASIS FOR DEVELOPING A TAILORED ONLINE LEARNING PLATFORM - Fitria Rahmawati; Dewanti Ratna Pertiwi; Sittie Noffaisah B. Pasandalan (University of Kuningan, 2025)
This study aims to analyze the needs of Adisutjipto-Aerospace Institute of Technology (ITDA) Yogyakarta students on online learning as the basis for the creation of an online learning platform. The research focused on and investigated 1) how students perceive the implementation of synchronous and asynchronous online learning in terms of content and structure; and 2) the students' learning needs regarding learning mode and activity, teacher aspect, and technical aspect of the online learning implementation. A survey design and a questionnaire were employed for a total of 146 students from one Mechanical Engineering class and three Aerospace Engineering classes who were all enrolled in an English course. The number of samples taken from the entire population was 119, with a confidence level of 5% and randomly selected. It was found that the three most important aspects in online learning are that of teachers with a mean value of 3.266 (very high), followed by learning content and structure (mean value of 3.153) and technical (mean value of 3.127) which are high. The research revealed in an online learning platform, teachers have a crucial role in the learning process of the students and in having a holistic online learning implementation. The results became the basis for further developing the content and structure of ITDA’s online learning platform, ELENA.